2019
DOI: 10.1177/0961203319839486
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitivity and photoprotection in patients with lupus erythematosus

Abstract: Lupus erythematosus (LE) represents a spectrum of inflammatory autoimmune disease comprising varying clinical entities ranging from primary cutaneous to systemic disease. There is a clear relationship between ultraviolet irradiation (UVR) and the clinical manifestations of LE in both adult and pediatric populations. Although it has been established that UVR exacerbates pre-existing LE, it remains unclear whether UVR induces the development of the disease. This review serves to discuss effective photoprotective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The sun’s emission of full-spectrum UV radiation is implicated in causing DNA damage, apoptosis, autoantigen exposure, cytokine production, and systemic flare induction in SLE patients. 1 , 2 The newest SLE treatment guidelines strongly recommend counseling patients about effective protection from UV exposure using broad spectrum sunscreens. 3 Yet, one study found that sunscreen use was discussed in less than one percent of visits.…”
mentioning
confidence: 99%
“…The sun’s emission of full-spectrum UV radiation is implicated in causing DNA damage, apoptosis, autoantigen exposure, cytokine production, and systemic flare induction in SLE patients. 1 , 2 The newest SLE treatment guidelines strongly recommend counseling patients about effective protection from UV exposure using broad spectrum sunscreens. 3 Yet, one study found that sunscreen use was discussed in less than one percent of visits.…”
mentioning
confidence: 99%
“…Low vitamin D levels in SLE may be related to reduced sun exposure, as SLE patients exhibit photosensitivity. 42,43 Low vitamin D levels in SLE may also be related to corticosteroid treatment, 44 although not all authors agree. SLE patients may have low vitamin D levels due to hydroxychloroquine treatment, which may affect vitamin D metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These measures are crucial to prevent refractory CLE. In fact, studies on the photoprotective habits of lupus patients have shown an increased frequency of sunscreen utilization during years (14,15). However, not all patients with CLE use daily sun protection, not all apply the right dose and not all re-apply sunscreen during the day.…”
Section: Introductionmentioning
confidence: 99%